Community structure and carbonate production of a temperate rhodolith bank from Arvoredo Island, southern Brazil (Brazilian Journal of Oceanography, 2004)
A small (100,000 m²) rhodolith bank located at the Arvoredo Marine Biological Reserve (Santa Catarina, Brazil) has been surveyed to determine the main bank components, the community structure, and carbonate production rates. Data from five photographic transects perpendicular to Arvoredo Island shore were complemented with sediment samples and shallow cores, all collected by scuba diving. The main bank component is the unattached, nongeniculate, coralline red algae Lithophyllum sp., used as substrate by the zoanthid Zoanthus sp. Percentage cover of living and dead coralline algae, zoanthids and sediment patches account for nearly 98% of the investigated area. Classification and ordination of samples showed that differences in the proportion of live and dead thalli of Lithophyllum sp. determine the relative abundances of zoanthids. Results also indicate that similarity of samples is high and community gradients are subtle. Significant differences in percentage cover along transects are concentrated in the central portion of the bank. Low carbonate content of sediments from deeper samples suggests low rates of recruitment and dispersal of coralline algae via fragmentation. However, carbonate production of Lithophyllum sp ranging from 55-136.3 g m-2 yr-1 agrees with production rates reported for other temperate settings. In the long run, rhodolith density at Arvoredo Is. is likely to be dependent upon random dispersal of spores and/or fragments from other source areas.